Criminality, social cohesion and economic performance - Horst Entorf; Hannes Spengler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
The paper intends to contribute to a better understanding of the interactions between criminality, economic performance and social cohesion. We try to achieve this aim by evaluating the existing economic and criminological research and by carrying out own empirical investigation on the basis of international panel data sets from different levels of regional aggregation. Our empirical results with respect to the causes of crime clearly reveal the crime reducing potential of family cohesion and the link between crime and the labour market. Furthermore, we find that higher wealth is associated with higher rates of property crime and of drug-related offences. Drug offences themselves turn out to be robust factors of property crimes. Compared to studies assessing the causes of crime, investigations on its consequences are relatively rare. In our analysis, we investigate the impact of crime on economic performance. We find evidence that employment as well as GDP growth rates are negatively affected by the regional incidence of criminality.
Keywords: K42; 330; Crime; socio-economic factors; demographics; European panel data; Kriminalität; Soziale Lage; Arbeitsmarkt; Familiensoziologie; Kriminalitätsökonomik; Wirtschaftswachstum; Schätzung; EU-Staaten